2017
DOI: 10.1177/0269215517695857
|View full text |Cite
|
Sign up to set email alerts
|

The Nottingham Fatigue after Stroke (NotFAST) study: factors associated with severity of fatigue in stroke patients without depression

Abstract: Objective: To identify factors associated with post-stroke fatigue in a sample of stroke survivors without depression. Design: Cross-sectional cohort study. Setting: Recruitment was from four stroke units in the UK. Subjects: Participants were assessed within four to six weeks of first stroke; those with high levels of depressive symptoms (score ⩾7 Brief Assessment Schedule Depression Cards) were excluded. Main measures: Participants were assessed after stroke on the Fatigue Severity Scale of the Fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
3
25
0
1
Order By: Relevance
“…Three cross-sectional surveys were embedded within cohort studies 91 , 94 , 97 . Only one of the studies (NotFAST) had a follow-up report 81 85 . Details of all studies are reported in Table 3 as well as the Extended data .…”
Section: Resultsmentioning
confidence: 99%
“…Three cross-sectional surveys were embedded within cohort studies 91 , 94 , 97 . Only one of the studies (NotFAST) had a follow-up report 81 85 . Details of all studies are reported in Table 3 as well as the Extended data .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we investigated the factors affecting fatigue at four to six weeks following stroke onset (n=268); these results have been reported in detail elsewhere (9). In summary, 115 (43%) participants reported fatigue, of whom 71 (62%) identified this as a post-stroke symptom.…”
Section: Introductionmentioning
confidence: 87%
“…NotFAST was a multi-centre, longitudinal cohort study; the methodology has been reported previously (9). Participants were recruited from four UK inpatient stroke services Participants were ineligible if they were unable to read or speak English sufficient to complete questionnaires or had a documented diagnosis of dementia.…”
Section: Methodsmentioning
confidence: 99%
“…Potential interviewees were identified from participants in the NotFAST study (Drummond et al, 2017). This was a multi-centre longitudinal cohort study to investigate post-stroke fatigue and its associated factors in patients who did not have high levels of depressive symptoms or aphasia.…”
Section: Designmentioning
confidence: 99%
“…The aim of the present study was to explore the day-to-day fatigue-related experiences and perspectives of participants who reported high levels of fatigue at six months following stroke in the Nottingham Fatigue After Stroke (NotFAST) study (Drummond et al, 2017).…”
Section: Introductionmentioning
confidence: 99%